The Louisville Twin Study: Past, Present and Future. (31st December 2019) - Davis, Deborah W.; Turkheimer, Eric; Finkel, Deborah; Beam, Christopher; Ryan, Lesa
Abstract: The Louisville Twin Study (LTS) is nationally recognized as one of the largest and most comprehensive studies of child development related to multiple birth status. The LTS is unique because of the extensive longitudinal face-to-face assessments, the frequency of data collection, the inclusion of data on additional family members (i.e., parents, siblings, grandparents; and later, twins' own spouses and children), and the variety of data collection methods used. Data preservation efforts began in 2008 and are largely complete, although efforts are ongoing to obtain funding to convert the electronic data to a newer format. A pilot study was completed in the summer of 2018 to bring the twins, who are now middle-aged, back for testing. A grant is currently under review to extend the pilot study to include all former participants who are now ≥40 years of age. Opportunities for collaboration are welcome.